Facilitating the application of auditors' underlying skeptical disposition: The relationship between trait skepticism and basic human values. Issue 1 (8th January 2020) - Khan, Jahanzeb; Harding, Noel
Abstract : Purpose: Motivated by ongoing calls for auditors to exercise an elevated level of professional skepticism, this paper aims to examine the relationship between basic human values (values) and an underlying skeptical disposition (trait skepticism). Understanding the values that are associated with levels of trait skepticism will help in the design of audit environments that make the application of an underlying skeptical disposition more likely. Design/methodology/approach: A survey was administered in which 140 postgraduate auditing students responded to the Schwartz value survey to measure the relative importance of different values, and the Hurtt trait skepticism scale to measure trait skepticism. The relative importance of the ten values was regressed against trait skepticism. Findings: This study finds that the importance placed in the values of tradition and power, relative to other values, is negatively associated with levels of trait skepticism. Research limitations/implications: The use of postgraduate auditing students as participants may limit the generalizability of the study's findings. Practical implications: Qualified by the need for future research to test the generalizability of the findings to an audit practitioner sample, the results of this study suggest that auditors with higher levels of trait skepticism may experience negative affect in environments that emphasize values of power and tradition. To the extent that current audit environments emphasize tradition and power, the results may help explain why trait skepticism is not consistently reflected in audit judgments and actions. Originality/value: The affective implications of the environment within which auditors exercise professional skepticism is emerging as an important area by which to understand and improve audit quality. By identifying the values that those with a high skeptical disposition place relatively less importance in, this study informs an understanding of the circumstances where an underlying skeptical disposition is more or less likely to be reflected in auditor judgments and actions.